Priority concerns for people with intellectual and developmental disabilities during the COVID-19 pandemic - Sam Tromans; Michael Kinney; Verity Chester; Regi Alexander; Ashok Roy; Josemir W. Sander; Harry Dudson; Rohit Shankar (BJPsych Open, 2020)
Background The approach taken to support individuals during the coronavirus disease 2019 (COVID-19) pandemic needs to take into account the requirements of people with intellectual disabilities and/or autism, who represent a major vulnerable group, with higher rates of co-occurring health conditions and a greater risk of dying prematurely. To date, little evidence on COVID-related concerns have been produced and no report has provided structured feedback from the point of view of people with intellectual disabilities and/or autism or of their family/carers.